1967
DOI: 10.1111/j.1745-3984.1967.tb00572.x
|View full text |Cite
|
Sign up to set email alerts
|

Using Item Analysis to Improve Tests

Abstract: Every major textbook in measurement discusses the improvement of a test through the use of item statistics. Most students taking a course in test construction remember that item analysis can be useful in item selection decisions. Unfortunately, they tend to forget that item analyses can also be useful for item revision. Too frequently a person doing an item analysis of a multiple-choice test fails to go beyond computing the item difficulty and discrimination indices. When only this superficial analysis is comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

1970
1970
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 2 publications
0
12
0
1
Order By: Relevance
“…To assess the difficulty and item discrimination, we completed a test item analysis on the MCQs. 23,24 Next, we determined item difficulty by dividing the number of participants answering the question correctly by the total number of participants. By subtracting the novice item difficulty from the expert item difficulty, we determined the item discrimination index.…”
Section: Pupil Data Recording and Analysesmentioning
confidence: 99%
“…To assess the difficulty and item discrimination, we completed a test item analysis on the MCQs. 23,24 Next, we determined item difficulty by dividing the number of participants answering the question correctly by the total number of participants. By subtracting the novice item difficulty from the expert item difficulty, we determined the item discrimination index.…”
Section: Pupil Data Recording and Analysesmentioning
confidence: 99%
“…Besides, learning becomes more interactive as lecturers are able to present feedbacks to students which could facilitate students to improve on those areas. Thus, in the item analysis, it has item revision [11] allows to identify items too difficult or too easy to differentiate between students who have learned the content of the subject and those who have not. The focus here is not just on the lecturers but it involves the students and the items too when it comes to item analysis.…”
Section: Discussion Of the Findingsmentioning
confidence: 99%
“…Items analysis allows us to observe the item characteristics and to improve the quality of the test. In the item analysis, it has item revision [11] allows to identify items too difficult or too easy to differentiate between students who have learned the content of the subject and those who have not. It can also to identify the questions that have distracters not credible.…”
Section: Benefits Of Item Analysismentioning
confidence: 99%
“…Furthermore, faculty need to be helped to use item analysis to help revise and improve items, in addition to selecting items. For example, Lange, Lehmann, and Mehrens (1967) found that it took about five times as long to develop a new psychology test item as to revise a n old one, using item analysis, and the revised item was more strongly related to course achievement.…”
Section: Methods Of Assessment or Measurementmentioning
confidence: 99%